The STATE AND GLOBAL SPORT GOVERNANCE: ANALYZING THE TRIANGULAR RELATIONSHIP AMONG THE FIFA, KEMENPORA RI, AND THE PSSI - Indra Kusumawardhana; Muhammad Badaruddin (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2018)
Discussion on the power interplay between global sport governance and state-level sport management in Indonesia enriches discourse on the relation between globalization and nation-stateâ€™s sovereignty. This Indonesiaâ€™s case is an exceptional, since it is representing triangular relationship among FÃ©dÃ©ration Internationale de Football Association (FIFA), the Indonesian Ministry of Youth and Sport (Kemenpora RI), and the Football Association of Indonesia (PSSI) which creates protracted dispute among football stake holders in Indonesia. This paper focus on the case of the Indonesian Kemenporaâ€™s decision to suspend the PSSI activities, which raised reaction of the FIFA by banning Indonesiaâ€™s participation in the global football agenda managed by FIFA. Departing from the abovementioned context and perspectives, the purpose of this essay is to answer the questions about the significance of a nation-stateâ€™s sovereignty to govern its domestic football issues, as well as answering the question of the global football governanceâ€™s power over the national football association. In answering these questions, this paper will draw dynamics relation among domestic political powers which contribute to the internal dispute inside the PSSI in the first part. This paper will also portray the global context by describing on how the FIFA exercises its â€˜global authorityâ€™ by imposing sanction to the member which is â€˜cooptedâ€™ by the domestic political power for the second part. Finally, in the third part, this paper will discover the power interplay among these three actors until the recent progress of this case which seems to prove the effective power exercised by the FIFA as a global football governor. Abstrak Diskusi mengenai interaksi kekuasaan antara tata kelola pemerintahan dunia di bidang olahraga dengan pranata manajemen olahraga pada level negara di Indonesia memperkaya diskursus terkait inter-relasi antara globalisasi dengan kedaulatan negara. Distingsi kasus Indonesia terletak pada interaksi triangular antara FÃ©dÃ©ration Internationale de Football Association (FIFA), Kementerian Pemuda dan Olahraga Republik Indonesia (Kemenpora RI), dan Persatuan Sepak Bola Seluruh Indonesia (PSSI) yang mengundang sengketa berkepanjangan antara pihak-pihak terkait dalam penyelenggaraan sepak bola di Indonesia. Artikel ini fokus pada dinamika pasca keputusan Kemenpora RI untuk melarang kegiatan PSSI, dimana keputusan tersebut memantik reaksi dari FIFA dengan membekukan hak partisipasi Indonesia di seluruh agenda sepak bola global yang dikelola oleh FIFA. Bertolak dari konteks dan cara pandang ini, tujuan utama dari artikel ini adalah untuk menjawab pertanyaan terkait signifikansi eksistensi kedaulatan negara dalam mengelola permasalahan sepak bola domestik, sekaligus mengungkap kekuasaan tata kelola sepak bola global terhadap asosiasi sepak bola nasional. Dalam menjawab pertanyaan ini, pada bagian pertama, artikel ini akan menelaah dinamika interaksi antara kekuatan-kekuatan politik domestik yang berkontribusi di dalam sengkarut kasus PSSI. Selain itu, artikel ini juga akan menangkap konteks global dengan mendeskripsikan kapasitas FIFA dalam mengartikulasikan otoritas global-nya dengan menjatuhkan sanksi terhadap anggota FIFA yang terkooptasi oleh kepentingan politik domestik. Sedangkan pada bagian akhir, artikel ini akan mengungkap interaksi kekuasaan antara tiga aktor di dalam kasus ini untuk membuktikan kekuasaan FIFA sebagai representasi dari â€œglobal football governorâ€. Kata kunci: Global Governance, Negara-Bangsa, Sepak Bola, Kemenpora RI, PSSI, FIFA.